2007
DOI: 10.1136/ard.2006.068676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxychloroquine on the survival of patients with systemic lupus erythematosus: data from LUMINA, a multiethnic US cohort (LUMINA L)

Abstract: Objective: In patients with systemic lupus erythematosus (SLE), hydroxychloroquine prevents disease flares and damage accrual and facilitates the response to mycophenolate mofetil in those with renal involvement. A study was undertaken to determine whether hydroxychloroquine also exerts a protective effect on survival. Methods: Patients with SLE from the multiethnic LUMINA (LUpus in MInorities: NAture vs nurture) cohort were studied. A case-control study was performed within the context of this cohort in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
325
2
22

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(362 citation statements)
references
References 28 publications
13
325
2
22
Order By: Relevance
“…There is evidence that supports the use of antimalarials for the prevention of flares or recurrences (13,14). Sixtytwo percent of our patients who achieved remission were taking antimalarials.…”
Section: Discussionmentioning
confidence: 62%
“…There is evidence that supports the use of antimalarials for the prevention of flares or recurrences (13,14). Sixtytwo percent of our patients who achieved remission were taking antimalarials.…”
Section: Discussionmentioning
confidence: 62%
“…In multivariate analysis, use of HCQ was associated with a reduced risk of developing new damage. The LUMINA Study Group showed that use of HCQ was associated with a greater survival rate in 608 SLE patients in a case-control study (6). The effect of HCQ on survival was also observed in the observational, prospective cohort study by Ruiz-Irastorza et al (7).…”
Section: To the Editormentioning
confidence: 60%
“…However, finding improved survival in SLE patients who used antimalarials versus those who did not could be confounding by indication, where perhaps only those patients with mild SLE were prescribed antimalarials (i.e., those with skin and joint involvement, mucositis, and mild constitutional symptoms) compared to those presenting with major organ involvement who received strong immunosuppressives and high doses of steroids. We agree that clinicians should use knowledge from the literature and their clinical experience when treating SLE and recognize the benefits of antimalarial treatment, such as a steroid-sparing effect in a randomized trial (6).…”
Section: Replymentioning
confidence: 99%
“…This is an issue of critical importance in SLE because HCQ therapy associates with a myriad of benefits in a serious, potentially fatal condition 4,5 .…”
Section: To the Editormentioning
confidence: 99%